Association of protein intakes and variation of diet‐scalp hair nitrogen isotopic discrimination factor in Papua New Guinea highlanders. Issue 3 (14th July 2015) - Naito, Yuichi I.; Morita, Ayako; Natsuhara, Kazumi; Tadokoro, Kiyoshi; Baba, Jun; Odani, Shingo; Tomitsuka, Eriko; Igai, Katsura; Tsutaya, Takumi; Yoneda, Minoru; Greenhill, Andrew R.; Horwood, Paul F.; et al.
ABSTRACT Objectives: We present new nitrogen isotopic discrimination factor between diets and scalp hairs (Δ15NHair‐Diet: δ15NHair – δ15NDiet) for indigenous residents in three communities in the Papua New Guinea Highlands who consumed various amounts and qualities of protein. The Δ15N is important for precise evaluation of the dietary habits of human populations; in both contemporary and traditional lifestyles. Several hypotheses have been proposed regarding factors that affect Δ15N values, based largely on observations from animal feeding experiments. However, variations and factors controlling Δ15N in humans are not well understood, mainly due to the difficulty of controlling the diets of participants. Materials and Methods: These residents were studied because they have maintained relatively traditional dietary habits, which allow quantitative recording of diets. Δ15N was estimated by comparing hair δ15N values to mean dietary δ15N values calculated from the recorded intake of each food item and their δ15N values. Results: The results showed that: i) there was a significant difference in Δ15N among study locations (3.9 ± 0.9‰ for most urbanized, 5.2 ± 1.0‰ for medium and 5.0 ± 0.9‰ for least urbanized communities; range = 1.2–7.3‰ for all participants); and ii) estimated Δ15N values were negatively correlated with several indicators of animal protein intake (% nitrogen in diet: range = 0.9–7.6%). Discussion: We hypothesize that a combination of several factors, which presumably included urea recycling and amino acid and protein recycling and/or de novo synthesis during metabolic processes, altered the Δ15N values of the participants. Am J Phys Anthropol 158:359–370, 2015. © 2015 Wiley Periodicals, Inc.